The two but rule the negative thinking into positive solutions - Wolpert, John (Ascent Audio, 2024)
"In The Two But Rule: Turn Negative Thinking Into Positive Solutions veteran tech innovator John Wolpert delivers an exciting, hands-on guide to using the principles of Momentum Thinking to get you-and your organization-unstuck. You'll learn how to build unstoppable velocity for your big idea, product, or strategy as you blast through the endless objections and counterarguments that bedevil every innovator and changemaker. You'll discover how to address common ""but"" complaints, like ""But that's too expensive,"" or ""But that won't work,"" at the same time as you refine your idea and polish it into a gem worthy of attention and implementation. In the book, you'll also find explanations for why a ""but"" statement should always be followed by another ""but"" statement; discussions of why ""toxic positivity"" and blind optimism can be just as harmful as constant naysaying; and step-by-step strategies for transforming momentum-killing objections into momentum-boosting innovation rocket fuel. A can't-miss resource for managers, executives, directors, and business leaders everywhere, The Two But Rule is also perfect for product managers, professionals in any field, government and academic leaders, and anyone else ready to successfully tackle their most stubborn and intractable problems.".
Online resource; title from title details screen (O'Reilly, viewed February 05, 2024)
Keywords: Problem solving; Thought experiments; Thought and thinking; Résolution de problème; Expériences de pensée; Pensée; thinking; Audiobooks; Livres audio